Contrasting diversity and temporal patterns in leaf and root microbiome of two nearby temperate Zostera marina meadows - E. Teira; A. Díaz-Alonso; E. Fernández; M. Pérez-Lorenzo; E. Delgadillo-Nuño; C. Mendoza-Segura; J. Severino P. Ibánhez; P. Beca-Carretero (Environmental Microbiome)
Abstract Background The Zostera marina microbiome plays a crucial role in meadow functioning and resilience. We aim at testing if the microbial communities of Z. marina leaves and roots exhibit distinct diversity and succession patterns associated to distinct environmental conditions and anthropogenic pressures. Site-specific and temporal changes of Z. marina leaf and root microbiomes were assessed in the urban beach of Bouzas and the rural beach of Cesantes in NW Spain from March 2021 to March 2022. Results The prokaryotic microbiome from leaves significantly differed from that in roots, and 33% of the OTUs were shared by both tissues. Significant differences in taxonomic composition were found between Cesantes and Bouzas, yet about half of the taxa were common to both locations, suggesting a host-specific core microbiome. Prokaryote diversity in roots was significantly higher than in leaves, and significantly higher in Bouzas than in Cesantes, while the diversity in leaves was higher in Cesantes. In Z. marina leaves, the dominant order Granulosicoccales was more abundant in Bouzas than in Cesantes, which could be indicative of anthropogenic pressures. Desulfobacterota was the dominant microbial group in roots, especially in summer. Many microbial taxa associated to the roots were positively correlated with plant growth, suggesting a positive effect of root microbiome on the plant. An apparent succession pattern was observed in the leaf and, to a lesser extent, root microbiomes in Bouzas, with communities from the beginning of the growing season (March) strongly resembling between the two sampling years. By contrast, leaf and root microbiomes in March largely differed between sampling years in Cesantes, suggesting an alteration on the meadow status, which could be associated to extensive macroalgae proliferation. The relative abundance of Crenarchaeota, Desulfobacterota, Campylobacterota, Spirochaetota, and Modulibacteria in Z. marina roots was relatively higher in Cesantes than in Bouzas, suggesting a more active role of N2 fixation, nitrification and S cycling in Cesantes. Conclusions Our results suggest that the seagrass microbiome may respond to environmental conditions and suggest that the temporal monitoring of the prokaryotes associated to roots and leaves may be a valuable tool to assess the seagrass meadow ecological and conservation status.